The assessment of depression in people with multiple sclerosis: a systematic review of psychometric validation studies. Issue 1 (December 2016) - Hind, Daniel; Kaklamanou, Daphne; Beever, Dan; Webster, Rosie; Lee, Ellen; Barkham, Michael; Cooper, Cindy
Abstract Background The prevalence of depression in people with multiple sclerosis (PwMS) is high; however, symptoms common to both conditions makes measurement difficult. There is no high quality overview of validation studies to guide the choice of depression inventory for this population. Methods A systematic review of studies validating the use of generic depression inventories in people with MS was conducted using MEDLINE and PsycINFO. Studies validating the use of depression inventories in PwMS and published in English were included; validation studies of tests for cognitive function and general mental health were excluded. Eligible studies were then quality assessed using the COSMIN checklist and findings synthesised narratively by instrument and validity domain. Results Twenty-one studies (N = 5, 991 PwMS) evaluating 12 instruments were included in the review. Risk of bias varied greatly between instrument and validity domain. Conclusions The review of validation studies was constrained by poor quality reporting and outcome reporting bias. Well-conducted evaluations of some instruments are unavailable for some validity domains. This systematic review provides an evidence base for trade-offs in the selection of an instrument for assessing self-reported symptoms of depression in research or clinical practice involving people with MS. We make detailed and specific recommendations for where further research is needed. Trial Registration PROSPEROCRD42014010597